ANALISIS PENGARUH CITRA DESTINASI DAN MOTIF BERWISATA TERHADAP TINGKAT KEPUASAN WISATAWAN LANJUT USIA - DANANJAYA, I MADE DANNY; KENCANA, I PUTU EKA N.; SUKARSA, I KOMANG GDE (E-Jurnal Matematika; Vol 6 No 2 (2017), 2017)
The purpose of this research is to know the influence of the image of the destination towards internal motivation and external motivation, internal motivation and external motivation against travelers, the influence of taourist motivation towards the stratification of tourists holidaying in the village of Sanur. The population in this research is the elderly tourists on vacation to the village of Sanur with sample as much 100 sample and sample “technique used is Accidentalsampling techniques. This research method using Partial Least Square with 3 variables second order in the variable image of tourist destination, motivation, satification of tourists and 6 first orde variable the explain the motivation variable satisfaction of tourists and travelers.The results of the research show that the image of destinations likely to affect external motivation path coefficient with a value amounting to 0.939 on the tourist motivation more dominant external motivation that affect the value of the coefficient of 0.836. While the motivations of tourist proved to influence that satisfaction of travelers with coefficients of 0.402.